Improvement on corrosion resistance of gypsum for ceramics molding with soluble salts. (March 2021) - Zhang, Mingtao; Zhao, Min; Peng, Jiahui; Liu, Xianfeng; Huang, Qian; Zhao, Liang
Abstract: Dissolution of dihydrate gypsum and severe chemical corrosion are the principal causes of short working life of gypsum molds in slip casting technology. In this experiment, a new modification method was focused on the improvement of corrosion resistance on the premise of ensuring water absorption and mechanical strength. The effects of three soluble salts (barium chloride, sodium phosphate and sodium oxalate) on various properties of gypsum molds were evaluated using three different methods, which included solution mixing, immersing and coating. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to evaluate the phase transformations, structures and morphologies. Results revealed that immersing hardened sample into sodium oxalate solution effectively enhanced the corrosion resistance at the optimum concentration of 1.8 wt%. The water-saturated flexural strength and softness coefficient were increased by 36.7% and 22.2%, respectively. Calcium oxalate was produced by chemical reaction between dissolved Ca 2+, SO4 2− and sodium oxalate. Calcium oxalate monohydrate (COM) was crystallized after water evaporation and the crystals accumulated on the outer surfaces of hardened pastes forming as waterproof film, which reduced the dissolution of dihydrate gypsum and further improved the corrosion resistance. Highlights: A new modification method by soluble salt on corrosion resistance is investigated. Immersing gypsum by Na2 C2 O4 solution is benefit for corrosion resistance enhancement. Waterproof COM crystallizes on outside surface protecting gypsum from corrosion.